Data for: A point-of-care assay for genotyping women prior to ovarian stimulation with recombinant or human menopausal gonadotropins in assisted reproduction - Nilsson, Mathilda; Hjelmér, Ida; Prahl, Alexandra; Nenonen, Hannah; Lundberg Giwercman, Yvonne (Lund University, 2025)
This dataset contains pseudonymized data on individuals undergoing assisted reproduction. It includes 1) n=400 women genotyped for FSHR N680S (rs6166), with demographic background and treatment-related parameters. Previously shared in SND: https://doi.org/10.5878/gb77-1e72 2) n=50 men and women investigated for assisted reproduction, genotyped for FSHR N680S.

Laboratory data: ΔRn values from Loop-mediated isothermal amplification (LAMP) real time PCR (SYBR with ROX reference). The genotyping dataset was analyzed with standard statistical software; LAMP real time PCR data were retrieved by software capable of reading fluorescence signals.

Detta dataset innehåller pseudonymiserade data på individer som genomgått assisterad reproduktion. Det inkluderar: 1) n = 400 kvinnor genotypade för FSHR N680S (rs6166), med demografisk bakgrund och behandlingsrelaterade parametrar. Tidigare delat i SND: https://doi.org/10.5878/gb77-1e72 2) n = 50 män och kvinnor undersökta för assisterad reproduktion, genotypade för FSHR N680S.

Laboratoriedata: ΔRn-värden från loopmedierad isotermisk amplifiering (LAMP) realtids-PCR (SYBR med ROX-referens). Genotypningsdatasetet analyserades med standardstatistisk programvara; LAMP-realtids-PCR-data hämtades med programvara som kan läsa fluorescenssignaler.
Data för: Ett patientnära test för genotypning av kvinnor inför ovarialstimulering med rekombinanta eller humana menopausala gonadotropiner vid assisterad reproduktion
Keywords: Receptors, Gonadotropin; Gonadotropinreceptorer; Point-of-Care Testing; Patientnära testning; Controlled ovarian stimulation; kontrollerad stimulering av äggstock; Loop-mediated isothermal amplification technique; LAMP-teknik (loop-mediated isotermal amplification); Medication and treatment; Medicinering och behandlingar; Medicinal Chemistry; Läkemedelskemi; Medical Genetics and Genomics; Medicinsk genetik och genomik